626 CARDIOVASCULAR DISEASE PHENOTYPES IN PREGNANCY: GESTATION, PERIPARTUM, AND LONG-TERM OUTCOMES. (15th December 2022) - Lucia Narducci, Maria; Graziani, Francesca; Ballacci, Federico; Scacciavillani, Roberto; Grandinetti, Maria; Delogu, Angelica Bibiana; Lillo, Rosa; Carolis, Sara De; Salvi, Silvia; Spera, Francesco Raffaele; Perna, Francesco; Vento, Giovanni; et al.
Abstract: Background: Maternal cardiovascular physiology is affected by changes that may be impaired in women with cardiovascular disease. Management of these pregnancies is challenging, as prevalence of late childbearing and of women with congenital heart disease achieving pregnancy is increasing. Objective: This single-center prospective study sought to evaluate the effects of maternal cardiovascular disease (CVD) on pregnancy outcome and, after birth, on maternal and fetal morbidity and mortality. Methods: 140 patients with cardiovascular disease prior to pregnancy (congenital or acquired) or cardiovascular disease developed during pregnancy were enrolled at our tertiary referral hospital between 2011 and 2021. Baseline data included cardiovascular risk factors, cardiological therapy, mWHO class in pregnancy, 12-lead EKG, and transthoracic echocardiography. Birth-related data included gestational age at delivery; neonatal weight, Apgar score at 1 and 5 minutes from birth; admission to neonatal ICU. A medium-to-long term follow-up of these patients was carried out by telemedicine. The primary endpoint was pregnancy outcome in terms of live births, week of delivery and fetal growth. Secondary endpoints included neonatal complications, maternal adverse cardiovascular events (death from cardiovascular causes, sustained arrhythmia, acute heart failure, postpartum cardiac surgery) and adverse obstetric events (spontaneous abortion, fetal loss, intrauterine death, neonatal death, SGA, prematurity, frequency of caesarean sections). Results: Six cohorts were identified: adult congenital heart disease (ACHD); arrhythmias; valvular heart disease (VHD); ischemic CVD; cardiomyopathies and myopericarditis (CM/MYO); aortic disease. Heart disease prior to pregnancy was the most common setting (88%), mainly including ACHD (54%), followed by VHD (15%) and arrhythmias (11%). The pregnancy-onset cardiovascular diseases (12%) were predominantly CM/MYO (53%), mainly peripartum dilated cardiomyopathy, followed by arrhythmias (35%). Intermediate and high-risk classes (mWHO II-III, III and IV) were observed in 94 patients (67%). There were no maternal deaths; acute heart failure occurred in 6% of patients with no significant difference between groups. Sustained arrhythmias were found in 7% of the total cases, with a significantly higher prevalence in the cohort with preexisting arrhythmia (p <0.05). Cardiac surgery was performed in 4% of the patients, all in the ACHD cohort. Live births were 135 (94%); fetal deaths were 5 (one spontaneous abortion, 3 fetal losses and one neonatal death). Caesarean section was performed in 74% of patients. The mean gestational age at birth was low in all groups (36.6 ± 4.6 weeks), as well as the neonatal weight in grams (2676.9 ± 698.3) and the percentile of neonatal weight (37.8 ± 25.2). Reduced LVEF was significantly associated with low neonatal weight in the mWHO risk class IV patients (p = 0.04). At a mean follow-up of 26 months, cardiac surgery was significantly higher in the group of aortic disease (50% in diseases of the aorta, 8% in the ACHD group, 7% in the CM/MYO group, no events in other groups; p = 0.007), despite the small sample under investigation. Conclusions: We provide insights of how, by strict and timely follow-up and a multidisciplinary approach implemented before pregnancy and throughout gestation, good outcomes can be achieved in pregnancies with congenital or acquired cardiovascular disease, despite the high prevalence of intermediate and high-risk patients.